Pengaruh Lingkungan Eksternal dan Perencanaan Strategis Terhadap Kinerja Usaha Mikro Kecil Menengah (UMKM) Konveksi di Bandar Lampung Dalam Perspektif Bisnis Islam - Handarto Ermawan; Any Eliza; Okta Supriyaningsih (STIKes Ibnu Sina Ajibarang, 2024)
In its development, the MSME sector is often faced with various problems caused by external factors. External constraints relate to access to sources of financing and a business climate that is less conducive to the development of small businesses, because so far it seems that various policies are more in favor of the large business sector, so that the various facilities provided by the government are mostly enjoyed by the large business sector. This research method used is a descriptive method with a quantitative approach. The sampling technique in this research used probability sampling with a simple random sampling method, the total sample was 97 MSME actors. Partially (T test) shows that the External Environment has a positive and significant influence on MSME Performance, Strategic Planning does not significantly influence MSME Performance, simultaneously (F test) it appears that the External Environment and Strategic Planning have a positive and significant influence on MSME Performance, and in an Islamic business perspective, External Environment and Strategic Planning consider ethical values ​​and sharia principles